Mutation at the entrance of the quinone cavity severely disrupts quinone binding in respiratory complex I - Jason Tae Yi; Panyue Wang; Alexei A. Stuchebrukhov (Scientific Reports, 2023)
Abstract In all resolved structures of complex I, there exists a tunnel-like Q-chamber for ubiquinone binding and reduction. The entrance to the Q-chamber in ND1 subunit forms a narrow bottleneck, which is rather tight and requires thermal conformational changes for ubiquinone to get in and out of the binding chamber. The substitution of alanine with threonine at the bottleneck (AlaThr MUT), associated with 3460/ND1 mtDNA mutation in human complex I, is implicated in Leber's Hereditary Optic Neuropathy (LHON). Here, we show the AlaThr MUT further narrows the Q-chamber entrance cross-section area by almost 30%, increasing the activation free energy barrier of quinone passage by approximately 5 kJ mol−1. This severely disrupts quinone binding and reduction as quinone passage through the bottleneck is slowed down almost tenfold. Our estimate of the increase in free energy barrier is entirely due to the bottleneck narrowing, leading to a reduction of the transition state entropy between WT and MUT, and thus more difficult quinone passage. Additionally, we investigate details of possible water exchange between the Q-chamber and membrane. We find water exchange is dynamic in WT but may be severely slowed in MUT. We propose that LHON symptoms caused by 3460/ND1 mtDNA mutation are due to slowed quinone binding. This leads to an increased production of reactive oxidative species due to upstream electron backup at the FMN site of complex I, thus resulting in a mt bioenergetic defect.